Cross-cultural adaptation and reliability of the Arabic version of Children's Hand-use Experience Questionnaire (CHEQ) - Ahmed Amer; Mahmoud A. Alomari; Gustav Jarl; Majd M Ajarmeh; Fathi Migdadi; Ann-Christin Eliasson; Liselotte Hermansson (SAGE Publishing, 2022)
Background Validated outcome measures are essential for assessment and treatment of children with disabilities. The Children's Hand-use Experience Questionnaire (CHEQ) was developed and validated for use in Western countries for children with unilateral hand dysfunction. This study aimed to perform a cross-cultural adaptation and investigate reliability for the Arabic CHEQ. Methods Translation and cross-cultural adaptation were performed in four phases: (i) forward-translation and reconciliation with feedback from parents and typically developing children from Jordan ( n = 14); (ii) backward-translation and review; (iii) cognitive debriefing with parents and/or their children with unilateral hand dysfunction ( n = 17); and (iv) review and proofreading. In the psychometric analyses, 161 children from Jordan (mean age [SD] 10y 8 m [5y 8 m]; 88 males) participated. Internal consistency was evaluated with Cronbach's alpha. Test-retest reliability was evaluated in 39 children with intraclass correlation coefficient (ICC) and weighted kappa (κ). Results Synonyms of four words were added to accommodate for different Arabic dialects. On average, 93% of children with unilateral hand dysfunction and their parents understood the CHEQ items. One response alternative, ' Get help ', to the opening question was unclear for 70% of the respondents and need further explanation. Two items about using a knife and fork were difficult to comprehend and culturally irrelevant. High internal consistency was demonstrated (Cronbach's alphas 0.94- 0.97) and moderate to excellent ICC (0.77-0.93). For 18 individual items, κ indicated poor to good agreement (κ between 0.28 and 0.66). Conclusions After the suggested minor adjustments, the Arabic CHEQ will be comprehensible, culturally relevant and reliable for assessing children with unilateral hand dysfunction in Jordan.